2012
DOI: 10.1242/jcs.119701
|View full text |Cite
|
Sign up to set email alerts
|

RARγ is Essential for Retinoic Acid Induced Chromatin Remodeling and Transcriptional Activation in Embryonic Stem Cells

Abstract: SummaryWe have utilized retinoic acid receptor c (gamma) knockout (RARc 2/2 ) embryonic stem (ES) cells as a model system to analyze RARc mediated transcriptional regulation of stem cell differentiation. Most of the transcripts regulated by all-trans retinoic acid (RA) in ES cells are dependent upon functional RARc signaling. Notably, many of these RA-RARc target genes are implicated in retinoid uptake and metabolism. For instance, Lrat (lecithin:retinol acyltransferase), Stra6 (stimulated by retinoic acid 6),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 76 publications
3
60
0
1
Order By: Relevance
“…Ϫ/Ϫ ES cells (38) to delineate the dynamics of the increase in Stra6 transcripts associated with RA treatment of murine ES cells in culture. We demonstrated that there is a 24-fold increase in Stra6 transcripts 48 h after RA addition in WT ES cells and that this increase does not occur in the RAR␥ Ϫ/Ϫ ES cells (Fig.…”
Section: The Increase In Stra6 Transcripts In Ra-treated Es Cells Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Ϫ/Ϫ ES cells (38) to delineate the dynamics of the increase in Stra6 transcripts associated with RA treatment of murine ES cells in culture. We demonstrated that there is a 24-fold increase in Stra6 transcripts 48 h after RA addition in WT ES cells and that this increase does not occur in the RAR␥ Ϫ/Ϫ ES cells (Fig.…”
Section: The Increase In Stra6 Transcripts In Ra-treated Es Cells Ismentioning
confidence: 99%
“…On a molecular level, RA mediates major changes in epigenetic marks on specific target genes (33)(34)(35)(36)(37). We recently showed that Stra6 transcripts are increased by RA treatment of embryonic stem (ES) cells and that this induction depends on RAR␥ (38).…”
mentioning
confidence: 99%
“…Because these genes are activated as early as 2 hours after RA addition to the cell aggregates, one can hypothesize that they are involved in the commitment of ESC to the neuronal lineage. A recent study conducted by Kashyap et al (Kashyap et al, 2013) has also shown that inactivation of RARc is associated with a reduced expression of several genes. However, the cells were not analysed under the same conditions as here and there was no correlation with neuronal differentiation.…”
Section: Discussionmentioning
confidence: 93%
“…(Right) Differential expression is also displayed with individual bars. Data were obtained from GSE43221 (Kashyap et al 2013).…”
Section: Crispr-cas9-mediated Gene Knockout In Mescsmentioning
confidence: 99%